Results of analysis of sediment core LV76-21 from Detroit Seamount - Sergey A Gorbarenko; Ivan S Kirichenko; Olga Psheneva; Aleksandr A Bosin (PANGAEA, 2025)
The sediment core LV76-21 was recovered from northwest of the Detroit Seamount (51°34'N, 167°15.7'E; water depth 2,769 m) using a gravity corer on the R/V “Akademik M.A. Lavrentyev” during joint Russian–Chinese expeditions in 2016. The core sediments were predominantly gray–olive gray terrigenous silty clay–clayey silt with rare sand. The sediment was coarser in the intervals of 144–167 and 434–456 cm. The upper 17 cm of the sediment was represented by an oxidized brown–gray-brown ooze. In the intervals 0–38 cm, 76–167 cm, 356–364 cm, 407–434 cm, 456–475 cm, and 519–546 cm, the sediments were represented by grayish-olive–olive weakly diatomaceous oozes. The sediments in the intervals of 0–144 cm and 519–546 cm were enriched with foraminifera shells, and sediments were weakly enriched with foraminifera at the intervals of 407–434 cm, 456–482 cm, and 546–557 cm. The lithological description shows three visible ash layers at depths of 364–366 cm, 397–404 cm, and 467–468.5 cm, with thin ash lenses at a depth of 477–479 cm.